On second thoughts: changes of mind in decision-making. Issue 5 (May 2022) - Stone, Caleb; Mattingley, Jason B.; Rangelov, Dragan
Abstract : The ability to change initial decisions in the face of new or potentially conflicting information is fundamental to adaptive behavior. From perceptual tasks to multiple-choice tests, research has shown that changes of mind often improve task performance by correcting initial errors. Decision makers must, however, strike a balance between improvements that might arise from changes of mind and potential energetic, temporal, and psychological costs. In this review, we provide an overview of the change-of-mind literature, focusing on key behavioral findings, computational mechanisms, and neural correlates. We propose a conceptual framework that comprises two core decision dimensions – time and evidence source – which link changes of mind across decision contexts, as a first step toward an integrated psychological account of changes of mind. Highlights: Changes of mind are observed during decision-making across a range of decision contexts. While changes of mind are relatively infrequent, they can serve to improve overall behavioral performance by correcting initial errors. Despite often improving performance, changes of mind incur energetic and temporal costs which can bias decision makers into keeping their original responses. Computational models of decision-making have demonstrated that changes of mind can result from continued evidence accumulation in the postdecisional period. Brain regions involved in metacognitive monitoring and affective processing are instrumental for change-of-mind behavior.